Variability in Response to Valsartan and Its Relationship With AGT M235T Genotype and Other Nongenetic Parameters Among a Sample of Hypertensive Individuals in Jordan: A Prospective Pilot Study - Hussein Alhawari; Yazun Jarrar; Malek Zihlif; Ayman Wahbeh; Sameeha Alshelleh; Khaled Ojjoh; Dalia Abdelrazaq; Hussam Alhawari (Health Science Reports)
ABSTRACT Background Valsartan, an angiotensin receptor antagonist widely used in hypertension and heart failure management, exhibits noticeable interindividual variation in response among hypertensive patients at the University of Jordan Hospital. The angiotensinogen (AGT) gene variant M235T, a functional genetic variant, influences the renin‐angiotensin system. Aims This study aims to explore interindividual variations in the valsartan response, considering genetics, particularly the AGT M235T variant, and other nongenetic factors. Methods This cohort study involved 95 unrelated Arabic Jordanians diagnosed with essential hypertension. Systolic (SBP) and diastolic blood pressure (DBP) measurements were taken at the initiation of 160 mg valsartan and after 1 month of treatment, assessing the valsartan response for each patient. Genetic analysis of AGT M235T was done using the polymerase chain reaction‐restriction fragment length polymorphism genotyping method. Anthropometric data were collected from University of Jordan Hospital computer records. Results Valsartan response assessment revealed diverse individual responses, the response to valsartan varied, with SBP reductions from < 10 to > 70 mmHg and DBP from < 2 to 30 mmHg. Patients with homozygous AGT M235T genotypes showed a less significant response (p < 0.05) to valsartan than heterozygous and reference genotypes. Additionally, results indicated a positive correlation of age (p = 0.03) and a negative correlation of height (p = 0.02–0.04) with the valsartan response. Regression analysis demonstrated that the patients' sex significantly influenced the valsartan response (p < 0.05). Conclusions This study identifies the AGT M235T genotype as a potential genetic contributor to variability in the valsartan response. Associations with age, height, and sex underscore the importance of considering genetic and demographic factors in tailoring valsartan therapy, for advancing personalized hypertension management.